2017
DOI: 10.1002/2017gc006876
|View full text |Cite
|
Sign up to set email alerts
|

3‐D basin‐scale reconstruction of natural gas hydrate system of the Green Canyon, Gulf of Mexico

Abstract: Our study presents a basin‐scale 3‐D modeling solution, quantifying and exploring gas hydrate accumulations in the marine environment around the Green Canyon (GC955) area, Gulf of Mexico. It is the first modeling study that considers the full complexity of gas hydrate formation in a natural geological system. Overall, it comprises a comprehensive basin reconstruction, accounting for depositional and transient thermal history of the basin, source rock maturation, petroleum components generation, expulsion and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
89
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(97 citation statements)
references
References 65 publications
7
89
1
Order By: Relevance
“…Using 10,000 Monte Carlo trials in 153 grid cells, we found that the volume of gas hydrate‐bound gas in the specific study area in Green Canyon ranged from 0.1 to 0.35 TCM. Most likely, ~0.22 TCM of gas at STP is hosted in gas hydrate in the study area, which is in close agreement with the result from Burwicz et al (). This result provides mutual credibility to the basin‐reconstruction 3‐D model by Burwicz et al () predominantly based on seismic data, and the more unconventional Monte Carlo simulation approach of this study based on empirical data set of gas hydrate occurrence from well logs.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Using 10,000 Monte Carlo trials in 153 grid cells, we found that the volume of gas hydrate‐bound gas in the specific study area in Green Canyon ranged from 0.1 to 0.35 TCM. Most likely, ~0.22 TCM of gas at STP is hosted in gas hydrate in the study area, which is in close agreement with the result from Burwicz et al (). This result provides mutual credibility to the basin‐reconstruction 3‐D model by Burwicz et al () predominantly based on seismic data, and the more unconventional Monte Carlo simulation approach of this study based on empirical data set of gas hydrate occurrence from well logs.…”
Section: Resultssupporting
confidence: 91%
“…Regional estimates of volume of gas hydrate‐bound gas have been carried out in small areas in Walker Ridge and Green Canyon areas in the northern Gulf of Mexico (Burwicz et al, ; Frye et al, ). Here we compare our results to Burwicz et al (), who used a comparatively small study area (Figure ). Burwicz et al () used comprehensive basin‐scale 3‐D modeling in a small study area of ~30 × 15‐km 2 dimension in Green Canyon (Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, enriched hydrates would form and clog the sediment pores preventing upward gas flow and further feeding hydrate growth above the BHSZ unless the thin clogged layer can be breached and the free gas flow can be restored (Xu & Ruppel, ). Burwicz et al () used this assumption and simulated significant gas hydrate saturations situated directly at the BHSZ by recharge of methane gas from decomposing gas hydrates using a three‐dimensional basin‐scale model.…”
Section: Models Of Methane Hydrate Formation In Geological Systemsmentioning
confidence: 99%
“…Concentrated hydrate deposits tend to form at and just above the base of gas hydrate stability (BGHS). This results in a sharp contrast in mechanical properties at the phase cementing hydrate occupy the pore space [10]. This contrast in physical properties is expressed in seismic data as bottom simulating reflections (BSRs), and BSRs remain our strongest remotely sensed indicator to infer the presence of GH [11].…”
Section: Introductionmentioning
confidence: 99%